Biodegradable Films Based on Gelatin and Montmorillonite Produced by Spreading - Manuel Fernando Coronado Jorge; Elisabete M. C. Alexandre; Christian Humberto Caicedo Flaker; Ana Mônica Quinta Barbosa Bittante; Paulo José do Amaral Sobral (International Journal of Polymer Science)
The main objective of this research was to study the properties of gelatin-based nanocomposites reinforced with the montmorillonite (MMT). The gelatin-based nanocomposites were prepared with solutions of 5 g of gelatin/100 g of film-forming solution, 0–10 g of montmorillonite/100 g of gelatin, and 30 g of glycerol/100 g of gelatin and were stored for 7 days at 58% relative humidity or in silica gel, depending on the type of assay. The reinforcement of gelatin-based nanocomposites with montmorillonite increased their thickness and decreased the moisture content. Tensile strength and Young’s modulus increased revealing more resistant and rigid nanocomposites. The increase in MMT concentration slightly changed the X-ray diffraction spectra indicating some loss of crystallinity and reinforced films presented less homogeneous structures. The montmorillonite concentration had not a clear effect on the thermal properties and FTIR spectra of nanocomposites were very similar to separated compounds.